Characterization of narrow-leaf lupin (Lupinus angustifolius L.) recombinant major allergen IgE-binding proteins and the natural β-conglutin counterparts in sweet lupin seed species. (1st April 2018) - Jimenez-Lopez, Jose C.; Foley, Rhonda C.; Brear, Ella; Clarke, Victoria C.; Lima-Cabello, Elena; Florido, Jose F.; Singh, Karam B.; Alché, Juan D.; Smith, Penelope M.C.
Highlights: Several newly identified polypeptides may constitute a new source of sensitization to lupin. Sera of lupin allergic patients exhibited differential IgE binding to lupin species and cultivars. IgE-binding capacity to five recombinant β-conglutin (rβ) isoforms was examined and compared. rβ2 may be a suitable candidate for diagnosis and immunotherapy to lupin allergy. Abstract: β-conglutin has been identified as a major allergen for Lupinus angustifolius seeds. The aim of this study was to evaluate the binding of IgE to five recombinant β-conglutin isoforms (rβ) that we overexpressed and purified and to their natural counterparts in different lupin species and cultivars. Western blotting suggested β-conglutins were the main proteins responsible for the IgE reactivity of the lupin species and cultivars. Newly identified polypeptides from "sweet lupin" may constitute a potential new source of primary or cross-reactive sensitization to lupin, particularly to L. albus and L. angustifolius seed proteins. Several of them exhibited qualitative and quantitative differences in IgE-binding among these species and cultivars, mainly in sera from atopic patients that react to lupin rather than peanut. IgE-binding was more consistent to recombinant β2 than to any of the other isoforms, making this protein a potential candidate for diagnosis and immunotherapy.